Oxygenator Impact on Ceftolozane and Tazobactam in Extracorporeal Membrane Oxygenation Circuits. Issue 3 (March 2020) - Cies, Jeffrey J.; Moore, Wayne S.; Giliam, Nadji; Low, Tracy; Enache, Adela; Chopra, Arun
Abstract : Objectives: To determine the oxygenator impact on alterations of ceftolozane/tazobactam in a contemporary neonatal/pediatric (1/4-inch) and adolescent/adult (3/8-inch) extracorporeal membrane oxygenation circuit including the Quadrox-i oxygenator (Maquet, Wayne, NJ). Design: A 1/4-inch and 3/8-inch, simulated closed-loop extracorporeal membrane oxygenation circuits were prepared with a Quadrox-i pediatric and Quadrox-i adult oxygenator and blood primed. Additionally, 1/4-inch and 3/8-inch circuits were also prepared without an oxygenator in series. A one-time dose of ceftolozane/tazobactam was administered into the circuits and serial preoxygenator and postoxygenator concentrations were obtained at 5 minutes, 1, 2, 3, 4, 5, 6, and 24-hour time points. Ceftolozane/tazobactam was also maintained in a glass vial and samples were taken from the vial at the same time periods for control purposes to assess for spontaneous drug degradation Setting: A free-standing extracorporeal membrane oxygenation circuit. Patients: None. Interventions: Single-dose administration of ceftolozane/tazobactam into closed-loop extracorporeal membrane oxygenation circuits prepared with and without an oxygenator in series with serial preoxygenator, postoxygenator, and reference samples obtained for concentration determination over a 24-hour study period. Measurements and Main Results: For the 1/4-inch circuit, there was approximately 92% ceftolozane and 22–25% tazobactam loss with the oxygenator in series and 19–30% ceftolozane and 31–34% tazobactam loss without an oxygenator in series at 24 hours. For the 3/8-inch circuit, there was approximately 85% ceftolozane and 29% tazobactam loss with the oxygenator in series and 25–27% ceftolozane and 23–26% tazobactam loss without an oxygenator in series at 24 hours. The reference ceftolozane and tazobactam concentrations remained relatively constant during the entire study period demonstrating the drug loss in each size of the extracorporeal membrane oxygenation circuit with or without an oxygenator was not a result of spontaneous drug degradation. Conclusions: This ex vivo investigation demonstrated substantial ceftolozane loss within an extracorporeal membrane oxygenation circuit with an oxygenator in series with both sizes of the Quadrox-i oxygenator at 24 hours and significant ceftolozane loss in the absence of an oxygenator. Tazobactam loss was similar regardless of the presence of an oxygenator. Further evaluations with multiple dose in vitro and in vivo investigations are needed before specific drug dosing recommendations can be made for clinical application with extracorporeal membrane oxygenation.